Fundamentals of digital logic with VHDL design - Brown, Stephen D. (McGraw-Hill, 2009)
Intended for an introductory course in digital logic design. The authors provide a balance between classical and modern design approaches. Basic concepts are introduced using simple log circuits, which are designed by using both manual techniques and modern CAD-tool-based methods.